IMPLEMENTATION of SuKMa-e JATIM APPLICATION TO INCREASE PUBLIC SATISFACTION INDEX IN EAST JAVA PROVINCE - Indah Novia Alfianita; Fedianty Augustinah; Dian Ferriswara; Sri Kamariyah (Journal of Governance and Public Administration, 2025)
The purpose of this study was to investigate how the application providing feedback on public services SuKMa-e Jatim, which stands for the East Java Electronic Community Satisfaction Survey, has an impact on increasing the community satisfaction index in East Java Province. It is expected that this application can improve the quality of public services by helping the community , as well as to assess the level of community satisfaction with the quality of services by public service providers. This study uses a quantitative method by sending questionnaires to people who use the application in various regions in East Java Province . To improve public services, the use of the SuKMa-e Jatim application contributes significantly to increasing the community satisfaction index. Influential factors include ease of use of the application, speed of response to community input, and transparency of information provided. This study also identified several challenges in using the application, such as the lack of understanding of technology among some people and the need to increase socialization about the benefits of the application. The conclusion of this study confirms that the SuKMa-e Jatim application has an important role in increasing satisfaction with customers, colleagues, and leaders in East Java Province. Recommendations are given to improve digital literacy training for the community and expand socialization about this application so that it can be utilized optimally. The results of this study are expected to be used as a reference in the development of other public service information systems in Indonesia.